Forecasting and tracking of project completion dateline using requirement traceability matrix in scrum - Tan, Eng Ian (2024)
Forecasting and tracking a project completion dateline plays a crucial role in project management and planning, as these are key factors in determining a project's success. SCRUM is an agile software development life cycle (SDLC) that is dynamic and flexible. In SCRUM methodology, the development life cycle is iterative, involving multiple iterations where each iteration focuses on a specific part of the system until its completion. This iterative nature accommodates dynamic requirements, as users are continuously involved in the software development process to ensure user satisfaction aligns with user requirements. After each iteration, or known as sprint, users evaluate the outcome, provide feedback, and necessary modifications are made to the requirements. As the requirements are changing over time, the problem of lack of formal documentations would also arise in the methodology itself. All these characteristics has made the process of forecasting and tracking the project completion dateline in SCRUM to be difficult.